Edukasi Investasi Masa Depan bagi Remaja di Yayasan Pendidikan Islam Tajaul Karomatu Kabupaten Tangerang - Didi Sunardi; Ratna Sari; Desi Prasetiyani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This community service program (PKM) was initiated in response to the limited financial literacy and investment awareness among adolescents. The activity aimed to improve students’ understanding of basic investment concepts, introduce safe and youth-appropriate investment instruments, and promote early financial planning habits. The PKM was conducted at Yayasan Pendidikan Islam Tajaul Karomatu, Tangerang Regency, on 7–8 October 2025 by six lecturers from Universitas Pamulang, involving 40 ninth-grade junior high school students. The implementation followed three stages: preparation, execution, and reporting. During the execution stage, several interactive methods were applied, including material presentation, hands-on practice, group discussions, and question-and-answer sessions to enhance student engagement and comprehension. The results show that participants demonstrated increased awareness of investment benefits, improved understanding of financial management, and greater interest in applying simple investment practices suitable for their age. Students also reported feeling more confident in identifying legal and trustworthy investment platforms compared to fraudulent schemes. Overall, the program successfully strengthened the participants’ financial literacy and provided early exposure to essential investment knowledge that supports responsible financial behavior.